Strategies for interpreting qualitative data - Feldman, Martha S., 1953- (Thousand Oaks, Calif. ; London : SAGE, 1995)
This useful book outlines four key strategies for interpreting qualitative data: ethnomethodology; semiotics; dramaturgy; and deconstruction. To demonstrate, the author applies the techniques of each method to a single data set, highlighting the differences in results.
"A SAGE university paper."
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Organizational sociology -- Research -- Case studies; Social sciences -- Research -- Case studies; Student housing -- Michigan -- Management -- Case studies; Qualitative research -- Case studies